A low-power and high-data rate passive RFID transceiver using 28-nm CMOS technology. Issue 12 (December 2015) - Abdo, Ibrahim; Odeh, Mutasem; Shahroury, Fadi R.
Abstract: This paper presents a low power, high data rate transceiver for passive RFID tags. Asymmetric communication link between the reader and the tag was employed to overcome the passive systems׳ power constraints while providing higher data rates. For the uplink, a low power, digital Impulse Radio Ultra-wideband (IR-UWB) transmitter was employed to send large amounts of data from the several tags to the reader while maintaining the low power requirements. The uplink can achieve data rates as high as 100 Mbps using BPSK modulation. On the other hand, the ISM band was used for the downlink. The downlink features slower data rate of 100 Kbps and utilizes a new modulation scheme that is more suitable for passive systems. The proposed transceiver was designed and simulated in 28-nm CMOS technology. Abstract : Graphical abstract: Abstract : Highlights: We present a low power, high data rate CMOS passive RFID transceiver. We introduce a new modulation scheme that is more suitable for passive systems. Asymmetric reader is used to obtain higher data rates under lower power consumption. The designed RFID transceiver achieves data rates as high as 100 Mbps at 4.55 pJ/b.